Narrative Review: Current Updates in The Treatment of Malaria - Edward Nangoy; Corry Novita Mahama; Angelina Stevany Regina Masengi (Syntax Idea)
Malaria is an infectious disease caused by the Plasmodium parasite and transmitted through the bite of female Anopheles mosquitoes. Although global efforts to control the disease have increased, malaria remains a major health threat, especially in developing countries. This study aims to identify recent developments in malaria treatment methods. This study uses a narrative review method. Data collection was carried out through a literature review by searching for relevant research articles, reports, and books from various scientific databases. The collected data were then analyzed in three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that updates in malaria treatment include the development of new drugs and combination therapies, prevention efforts through vaccines, more individualized treatment approaches, and community involvement in treatment programs. These initiatives provide new hope in the fight against malaria.